Association study of two functional single nucleotide polymorphisms of neuropeptide y gene with multiple sclerosis. (December 2016) - Mohammadi, Seyed Mahdi; Shirvani Farsani, Zeinab; Dosti, Rozita; Sahraian, Mohammad Ali; Behmanesh, Mehrdad
Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system characterized by brain inflammation, demyelination and axonal loss. Neuropeptide Y ( NPY ) has a critical role in the maintenance of homeostasis in the immune system and coping of stress condition. In the current study we analyzed 188 patients suffering from MS and 204 unrelated healthy controls for two functional single nucleotide polymorphisms (SNPs), NPY 20T > C (rs16139) and NPY -485 T > C (rs16147) using PCR-RFLP and Mismatch PCR-RFLP methods. Our results demonstrated that homozygocity in the minor allele for NPY -485 T > C polymorphism is associated with the MS risk in patients in compare with healthy controls (CC vs. TT, P = 0.033; CC vs. TT + TC, P = 0.02). In addition, by comparison with allele T, the frequency of NPY -485C allele was higher in cases than in control subjects and present increased risk of MS, but statistically significant was borderline ( P = 0.053). The stratification for disease progression revealed a significant difference in the allelic and genotypic distribution between subgroups of MS and controls. The frequency of the CC genotype and C allele was higher in the primary progressive MS patients when compared with control group (CC vs. TT, P = 0.019; CC vs. TT + TC, P = 0.008; C vs. T, P = 0.022). In addition, the frequency of CC genotype was higher in the relapsing remitting MS patients when compared with control group (CC vs. TT, P = 0.034; CC vs. TT + TC, P = 0.016). Haplotype analysis demonstrated that the haplotype 3 (CT) is more common in RR MS ( P = 0.041), and PP MS ( P = 0.031) than control group. In conclusion, the obtained results demonstrate the probable role of NPY SNPs in susceptibility to MS within the Iranian population. Highlight: The genetics variants of the NPY gene related to susceptibility to autoimmune diseases such as multiple sclerosis. SNP 485T > C in NPY increased susceptibility to primary progressive MS. Neuropeptide Y has an end-point mediator's role in nervous system for MS disease development or progress.